Does it Pay to Invest in Potable Water in the Developing World? Relationships Between External Financing and Economic Development in Sustainable Community‐Run Integrated Projects. (27th September 2012) - Sauer, Michael; Smith, Stuart; Clemens, Bruce
Abstract: This paper quantifies the impact of external aid channelled through a support agency that practises a participatory approach to development. Researchers compiled completed project data collected from the non‐governmental organisation (NGO) Agua del Pueblo and discovered a positive relationship between external funding for water development projects and resulting economic development. This paper discusses the importance of water development as a channel for achieving overall economic development and the importance of the participatory approach for community development projects. Copyright © 2012 John Wiley & Sons, Ltd.